상고실 진주종 의심 소견 및 급성 염증성 안면신경마비를 주소로 내원한 비인두강의 미만성 거대 B세포 림프종 1예 - 전민채(Min-Chae Jeon); 박소희(So-hee Park); 이동희(Dong-Hee Lee) (대한두개저학회지, 2021)
Malignant lymphoma is tumor of the immune system. It is mainly found in the lymph node but it can also originate from extranodal organs such as gastrointestinal tract, sinonasal tract, and etc. Because primary involvement of diffuse large B-cell lymphoma (DLBCL) of the middle ear is rare, otitis media and facial palsy are rare clinical presentation of DLBCL. We report a case of DLBCL in 65-year-old man, who developed otalgia, tinnitus and facial palsy. Computed tomography revealed a mass in the right mastoid, petrous apex and clivus. Nasopharyngeal deep biopsy and histopathological examination revealed DLBCL. This case highlights the importance of considering malignant lymphoma as one of the differential diagnosis in persistent otitis media and facial palsy. KCI Citation Count: 0